Quick Evaluation Study on Fourteen (14) Major Development Programmes in 33 Selected Districts of the 8 States Affected by Left Wing Extremism (LWE) Volume-III - Planning Commission (Planning Commission, 2012)
The Task Force on the Left Wing Extremism (LWE) entrusted Programme Evaluation Organization (PEO) of Planning Commission to conduct a "Quick Evaluation Study" on the implementation of 14 major development programmes in 33 districts spread over the 8 States of the country affected by LWE. Left Wing Extremists, operate in India in the space created by the absence of effective administrative and political institutions to deliver the benefits of development to all sections of the society. They take advantage of the discontent prevalent among the poor and exploited segments of local population and operate with their active support with a promise of an alternate and more responsive system of governance. The LWE movement is not merely a law and order problem but has deep socio-economic dimensions.
Programme Evaluation Organisation Planning Commission Government of India
Programme Evaluation Organisation Planning Commission Government of India